Enhancing Adolescent Physical Development Understanding: Evaluating the Impact of Word Search Puzzle Games on Student Mastery - Aly Imron; Deffri Anggara; Febrika Dwi Lestari; Rina Oktavia Simarmata; Pandu Adi Cakranegara (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to determine the effectiveness of the Word Search Puzzle game on students' mastery of concepts in adolescent physical development material. This type of research is classroom action research which is carried out in 2 cycles. The subjects of this research were 7th-grade students at Junior High School. Each cycle consists of 4 stages: planning, implementation, observation and reflection. Data collection uses interview techniques, observation sheets and test instruments. Data was analyzed descriptively qualitatively. The results of the research show that the word search puzzle learning media is effective in improving students' concept mastery abilities. As the data shows, the test results in cycle I were 71.47, and increased in cycle II by 80.29%. Furthermore, the concept mastery indicators also increased from initial observations, cycle I and cycle II. Thus, there is an increase in students' mastery of concepts from cycle I to cycle II.